Poverty In Bengkulu Province 2010-2017 - Aryati, Seri; Salsabila, Ghina; Thilfatantil, Muthia Hasna; Christianawati, Aprillia; Prima, Fitri Riswari (Universitas Negeri Semarang, 2019)
Bengkulu is one of the provinces with the highest poverty in Indonesia. The Poverty Gap Index in 2017 is also higher than Indonesia. The purpose of this research is to determine the development of poverty in Bengkulu Province in 2010-2017. The method used in this research is descriptive quantitative based on secondary data. The variables include the percentage of poor people, poverty gap index, poverty severity index and gini index. The results are analyzed descriptively with a macro analysis unit based on the district /city administration unit. The results of this research show that poverty in Bengkulu Province was increasing from 2010 to 2015 and then it’s decreasing until 2017, this increasing was caused by inflation that made the prices of needs increase. The lowest poverty rate is in Bengkulu Tengah District, while the highest level is in the southern part of Bengkulu Province includes Bengkulu Selatan Regency, Seluma Regency, Kaur Regency, and Bengkulu City.